A systematic review of the effects of strength training in patients with fibromyalgia: clinical outcomes and design considerations - de Azevedo Klumb Steffens R.* (2018)
BACKGROUND: Fibromyalgia (FM) is characterized by chronic and generalized musculoskeletal pain. There is currently no cure for FM, but palliative treatments are available. One type of treatment is strength training (ST). However, there is a need for more information on optimal training protocols, intensity, and volume needed to improve symptoms. The aim of this study was to analyze the effects of ST in the treatment of FM through a systematic review of experimental research. METHODS: Medical Subject Headings search terms and electronic databases including Scientific Electronic Library Online, PubMed, Science Direct, Web of Science, and Physiotherapy Evidence Database were used to identify studies. RESULTS: The inclusion criteria were met by 22 eligible studies. Most of the studies were conducted in the United States (36%), Finland (23%), Brazil (18%), and Sweden (18%). The studies showed that ST reduces the number of tender points, fatigue, depression, and anxiety, and improves sleep quality and quality of life in patients with FM. The intervention period ranged from 3 to 21 weeks, with sessions performed 2 times a week in 81.81% of the studies, at initial intensities of 40% of 1-repetition maximum. The repetitions ranged from 4 to 20, with no specific protocol defined for ST in FM. CONCLUSION: The main results included reduction in pain, fatigue, number of tender points, depression, and anxiety, with increased functional capacity and quality of life. Current evidence demonstrates that ST is beneficial and can be used to treat FM. TRIAL REGISTRATION: CRD42016048480.